Review on oral methotrexate in medical management of ectopic pregnancy: a 2 years experience in hospital Shah Alam - Jabarudin, Wan Nurul Ezyani Wan; Som, Normala Mohammad; Mohammad Daud, Afidatul Mardhiah; Shamsuddin, Nor Dalila; Yaacob, Nazian Hanna; Omar, Hamidah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study is to determine the success rate of oral methotrexate in Hospital Shah Alam for the past 2 years. Methods: This is a cross-sectional study using secondary data obtained from medical record office in Hospital Shah Alam on patients with ectopic pregnancy. A total of 35 patients who fulfilled the criteria for medical management were selected. They were prescribed with oral methotrexate with the dose of 60 mg given in 3 divided doses every 2 hours using the standard tablet of 2.5mg. Follow up was done at day 4, day 7 and till HCG level achieve less than 20 iu/litre. Results: 29 patients were successfully treated with oral methotrexate 60 mg (82.8%). Another 6 patients had to undergo laparoscopic surgery with confirmed leaking, ruptured tubal pregnancy. 4 patients needed second dose of Methotrexate due to rising HCG level and all of them were successfully treated after the second dose. The side effects of oral methotrexate were tolerated well by all patients. There are numbers of predictors for success which are the level of HCG <4000 iu/litre, size of mass <4cm, no abdominal pain during early presentation and decrease of HCG level in between day 4 to day 7 after oral methotrexate. Conclusions: The success rate of oral methotrexate for stable ectopic pregnancy is good making it a suitable option for clinical settings which has no specialised equipment to handle cytotoxic drugs.